2010
DOI: 10.1111/j.1468-2389.2010.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Extended Theory of Planned Behavior in Predicting Job Seeker Intentions to Use Job‐Search Websites

Abstract: Although use of the Internet for job searching is rapidly increasing, the motivations for using electronic recruitment (e-recruitment) services by job seekers have seldom been addressed. Derived from the extended theory of planned behavior, this study develops a research model for the empirical examination of factors affecting job seeker intentions to use job-search websites. Utilizing data collected from 174 participants in Taiwan, various relationships in the research model are tested using structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
92
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 55 publications
17
92
1
1
Order By: Relevance
“…Kwon and Wen [27] stated that perceived ease of use will have a positive effect on perceived usefulness and actual use of a social network service. In the study of Lin [29], perceived ease of use had a significant positive effect on attitude toward using jobsearch Web sites. Some studies have shown that the perceived enjoyment influences the perceived ease of use of a computer system or application [14,26,55], whereas some studies have shown that the perceived ease of use influenced the perceived enjoyment of the computer system or application [21,28].…”
Section: Perceived Ease Of Use (Peu)mentioning
confidence: 90%
“…Kwon and Wen [27] stated that perceived ease of use will have a positive effect on perceived usefulness and actual use of a social network service. In the study of Lin [29], perceived ease of use had a significant positive effect on attitude toward using jobsearch Web sites. Some studies have shown that the perceived enjoyment influences the perceived ease of use of a computer system or application [14,26,55], whereas some studies have shown that the perceived ease of use influenced the perceived enjoyment of the computer system or application [21,28].…”
Section: Perceived Ease Of Use (Peu)mentioning
confidence: 90%
“…Studies (e.g. Lin, 2010;Gopi & Ramayah, 2007;Blanchard et al, 2008) have been conducted in various contexts and there are adequate empirical evidences to show that perceived behavioural control has a significant impact on behavioural intention. In the context of financial decision making, Mahastanti and Hariady (2014) suggested that perceived behavioural control can be the only significant predictor for the investors' intention to invest in the stock market.…”
Section: Perceived Behavioural Control and Stock Market Intentionmentioning
confidence: 99%
“…The use of intention as a predictor of behaviour is grounded in the psychological literature and conceptual frameworks that develop it such as the Theory of Reasoned Action, Theory of Planned Behaviour and Technology Acceptance Model. Intention is considered a strong indicator of actual behaviour in various settings including job seeking behaviour, smoking cessation and technology uptake (Ajzen 1988, 1991, Bryce et al 2013Hsu and Chiu 2004;Lin 2010). In this current setting, the intention to report is central to the error management climate within the organisation as Van Dyck et al (2005) state that communication about errors constitutes the most important error management practice.…”
Section: Module 2: the Intention To Report Operational Risk Events Sumentioning
confidence: 99%